Novel hybrids of fluconazole and furanones: design, synthesis and antifungal activity - Borate, Hanumant B.; Sawargave, Sangmeshwer P.; Chavan, Subhash P.; Chandavarkar, Mohan A.; Iyer, Ramki; Tawte, Amit; Rao, Deepali; Deore, Jaydeep V.; Kudale, Ananada S.; Mahajan, Pankaj S.; Kangire, Gopinath S. (Bioorganic & Medicinal Chemistry Letters, 2011)
During our efforts to develop new antifungal agents, a number of hybrid molecules containing furanones and fluconazole pharmacophores were designed and synthesized. The new chemical entities thus synthesized were tested for their potential as antifungal agents against various fungal strains and it was observed that the compounds with general structure 7 were potent inhibitors of Candida albicans ATCC 24433, Candida glabrata ATCC 90030, Candida tropicalis ATCC 750 and Candida neoformans ATCC 34664 while the fluconazole analogues 12 exhibited antifungal activity against Candida albicans ATCC 24433 and Candida glabrata ATCC 90030. The structure-activity relationship for these compounds is discussed. The synthetic strategies used in the present work have potential to prepare a large number of compounds for further refinement of structures to obtain molecules suitable for development as antifungal drugs. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activity; Fluconazole; Furanones

One-step synthesis of 4-alkyl-3-aryl-2,6-dicyanoanilines and their use in the synthesis of highly functionalized 2,3,5,6,7-and 2,3,4,5,7-substituted indoles - Sawargave, Sangmeshwer P.; Kudale, Ananada S.; Deore, Jaydeep V.; Bhosale, Dattatry S.; Divse, Jaisingh M.; Chavan, Subhash P.; Borate, Hanumant B. (Tetrahedron Letters, 2011)
A three-component, one-step method for the synthesis of 4-alkyl-3-aryl-2,6-dicyanoanilines involving reaction of alkyl aldehyde, malononitrile and aryl aldehyde in presence of morpholine is reported. Highly functionalized 2,3,5,6,7- and 2,3,4,5,7-substituted indoles were prepared from these dicyanoanilines by reaction with ethyl bromoacetate. These substituted dicyanoanilines and indoles have a potential to be converted into various other compounds taking advantage of various functional groups present in these molecules. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; Dicyanoanilines; indoles; Malononitrile